Analisis Faktor Pengunduran Diri Karyawan pada Perusahaan PT. Midi Utama Tbk Branch Medan - Ria Septiana; Nuri Aslami (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
It is hoped that the results of this research can provide a better understanding which aims to analyze the factors that influence employee resignation at PT. MIDI Utama Tbk. Medan Branch. By understanding the factors that influence attrition, companies can take better action in retaining potential employees. Employee resignation is an important issue in human resource management, because it can have a negative impact on company productivity and recruitment costs. The research results show that there are several main factors that contribute to employee resignation at PT. MIDI Utama Tbk Branch Medan. These factors include dissatisfaction with working environment conditions, excessive workload, lack of career development opportunities, as well as communication and management problems. In addition, personal factors such as changes in family status also influence the decision to resign. By understanding these factors, companies can take more effective action in retaining potential employees and promoting a more positive work atmosphere. Efforts to improve communication, reduce excessive workload, and provide further career development opportunities can be effective strategies in reducing employee resignation rates.